Analisis Program Kerja Prodi Pbi Jurusan Tarbiyah STAIN Samarinda Tahun 2011-2015 - Shafa Shafa; Darwis Darwis (FENOMENA, 2013)
The research is to analyze some aspects that are being the attention in the working program analysis, such as: Reinforcing of vision, mission, goal and target, also achievement strategy; Tutor arrangement, leadership, management system, and giving a guarantee of quality; Related to university student  and graduate; Human resource; Curriculum, teaching and learning, and academic situation; Funding, means and infrastructure, also information system; Research, servicing/ public service, and cooperation. The research goals are: (1) To dig what programs that has been arranged by English Department of STAIN Samarinda in academic year 20111-2015; (2) To know what steps that is taken by English Department in implementing the working program; (3) To analyze the strength/ opportunity and challenge that will be faced by English Department based on the working program that has been arranged. The research isdescriptive-qualitative that using some techniques of data collecting, namely: interview, observation, and documentation. The research respondents are Vice Chairmanof Student University Affairs,Chairman of Tarbiyah Department, and English Department coordinator. Then the data collection is analyzed by using analysis of SWOT. The research summary is: The steps that is taken by English Department in implementing the working program such as: socializing the vision, mission, and strategy of English Department through brochure and leaflet distribution, optimalizing the cooperation with stakeholder such as school and region government through the programs of Tarbiyah Department, building an intensive communication with the leadership party to back up the working program, maximizing the calculation every year that oriented on the increase of study of program quality from the managerial aspect or the human resource. Nevertheless, the working program of English Department implementation from the extend time of 2011 to 2013 the applicability is still minimized and does not achieve 50% of it.